Spatial segregation as an impact of the development of mass housing areas in Pamulang – South Tangerang (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The fast growing of housing development in the peri-urban areas of big cities in Indonesia is a consequence of the limitation of land in urban areas. The economic value of land is increasingly expensive, making it unaffordable for lower-middle income people. One of the housing areas that is developing in the South of the Metropolitan City of Jakarta is the Pamulang - South Tangerang area. The development of housing clusters in this area takes place sporadically on a varying scale. These housing clusters use a "one gate system", so that there are barriers between housing clusters and non-cluster housing, public and social facilities around them. The impact of the physical spatial boundaries of the land of these housing clusters is the emergence of spatial segregation problems, such as socio-economic disparities, reduced social interaction between groups, limited access between housing clusters and increased social conflict. This needs serious attention in inclusive urban spatial planning.
Keywords: Cluster; Housing; Pamulang; Peri-urban; Spatial segregation